Effectiveness of Activated Carbon Solution in Reducing Odor in Cancer Patients in the Surgical Ward - Fatmawati Fatmawati; Ema Julita; Windu Reswari; Rahmadevita Septika; Milawati Milawati (GLOBAL HEALTH SCIENCE GROUP, 2025)
Cancer is a disease with a high incidence rate in the world and is the main cause of death, as well as causing complications, one of which is malignant wounds which cause an unpleasant odor due to the process of tissue necrosis and infection.. This study aims to determine the effectiveness of activated carbon solution in reducing odor in cancer patients in the surgical room of Dr. M. Djamil Padang General Hospital in 2025. This study uses a research designquasi experimental design with non-equivalent with control group design pre-post-test.The population of this study consisted of all patients treated in the surgical ward of Dr. M. Djamil Padang General Hospital. The sampling technique in this study was carried out usingtechnicianrandom block sampling. Using a sample of 60person Data were collected after obtaining ethical approval and hospital permission for cancer patients. Data collection was carried out by measuring wound odor using an activated charcoal solution.using the NRS-B (Numerical Rating Scale for Odor) score analysis was carried out using statistical testsMann Withnay (Non normal distribution). Research result The median odor score in the intervention group was5 (3-9),while in the control group was 6 (3-9).Statistical analysis with nonparametric tests shows the value ofp < 0,000, which indicates a statistically significant difference between the two groups. These results indicate that activated charcoal solution can significantly reduce odor scores compared to the group that did not receive intervention.. mark p < 0,000, which indicates that the difference in smell scores between pre-test and post-test in the intervention group is more significant than in the control group.This study shows that administering activated charcoal solution has a significant effect on reducing wound odor in cancer patients.The results of this study are expected to be the basis for developing evidence-based nursing practices in palliative care, particularly in the management of smelly cancer wounds.